(untitled) (Herald of the National Children’s Medical Center, 2025)
Numerous studies show that about 65% of modern schoolchildren have II, and more than 25% have III health groups, and only no more than 10% can be considered practically healthy. Postural disorders and scoliosis become a favorable background for the formation of diseases of various organs and systems, especially in high school students.